(untitled) (Journal of Engineering, 2007)
The Concept of Alienation has succeeded in being the main and most dealt phenomena and estate in the modern era , thus it was issued in different fields of knowledge such as Language , philosophy , Social and Psychological Sciences alongside the field of Architecture , and that caused the special pivot of the research and that was represented with ( Alienation in the Built Environment) . The Concept of Alienation consists of three main forms ( Physical/Spatial , Social and Psychological Alienation) ; The first can be defined as the rapture in the relationship between man and his surrounded built environment caused by the urban tissue disintegration, the latter effected on the built environment physical consistencies like the architectural symbols, beside it created some contradicted areas where chaotic and anonymat urban spaces were the main reasons for the lack of the social interaction and the spread of socially alienated people. The previous forms of alienation caused psychological disorder and conflict to men living within such fragmented built environment. Consequently these items were chosen for the purpose of application in the main pilot study alongside with two specified projects. The first is Hay Al-Siha in Dora area and the second is 9 Nissan in Al-Salhiya area both projects are residential areas which built in contemporary period. The main conclusion came out that the contemporary local built environment suffers from alienation crisis that appears with its three forms alternatively , depending on some secondary factors like social , economical , cultural and time factors, which is caused by innovation and renewal processes attached with rapid and sudden changes. These processes consist of discontinuity and rapture in the relationships that links its main elements like man-built environment and man-man relationship.